2018
DOI: 10.1021/acs.jmedchem.7b01672
|View full text |Cite
|
Sign up to set email alerts
|

G-Quadruplex Identification in the Genome of Protozoan Parasites Points to Naphthalene Diimide Ligands as New Antiparasitic Agents

Abstract: G-quadruplexes (G4) are DNA secondary structures that take part in the regulation of gene expression. Putative G4 forming sequences (PQS) have been reported in mammals, yeast, bacteria, and viruses. Here, we present PQS searches on the genomes of T. brucei, L. major, and P. falciparum. We found telomeric sequences and new PQS motifs. Biophysical experiments showed that EBR1, a 29 nucleotide long highly repeated PQS in T. brucei, forms a stable G4 structure. G4 ligands based on carbohydrate conjugated naphthale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
83
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 65 publications
(84 citation statements)
references
References 81 publications
(101 reference statements)
1
83
0
Order By: Relevance
“…The significant level of interest in G4 partly stems from its potential as a therapeutic target , , . Indeed, G4‐forming DNA and RNA sequences are not confined to the human genome but also observed in a host of other organisms including plants, bacteria, viruses and parasites . This provides many potential opportunities to exploit G4 for the development of new therapeutic strategies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The significant level of interest in G4 partly stems from its potential as a therapeutic target , , . Indeed, G4‐forming DNA and RNA sequences are not confined to the human genome but also observed in a host of other organisms including plants, bacteria, viruses and parasites . This provides many potential opportunities to exploit G4 for the development of new therapeutic strategies.…”
Section: Introductionmentioning
confidence: 99%
“…This provides many potential opportunities to exploit G4 for the development of new therapeutic strategies. Indeed, our own research groups and many others have reported work driven towards the identification of new G4 ligands as the basis of anticancer, and antiparasitic, therapies. The vast majority of G4 ligands employ rigid aromatic heterocyclic frameworks that are designed to π‐stack onto the large surface of the G‐tetrads .…”
Section: Introductionmentioning
confidence: 99%
“…Also, higher G4 frequency allows easier and more accessible targets for the current G4-ligands, which in general are not selective between G4s (22)(23)(24). As example, we recently published the results of a PQS search in several parasitic genomes whilst considering frequency, and identified numerous highly recurrent potential G4 candidates (25). Most of these had already been described in literature as G4-forming structures; yet other sequences were new, including EBR1 which is repeated 33 times in the genome of Trypanosoma brucei.…”
Section: Introductionmentioning
confidence: 99%
“…The sequence occurs in genomic regionscoding for several proteins including ac ysteinep eptidase and ap urine transporter. [9] G4st herefore present ap otential opportunity as at arget for novel antiparasitic therapies, for which there is an urgent need for further development. [11] The T. brucei parasite, responsible for the Human African Trypanosomiasis (HAT) disease, endangers 69 million people across Sub-Saharan Africa, [12,13] and existing therapies suffer from severe limitations including drastic side effects [14] and emerging drug resistance [15] in the parasitic strains.G 4l igands have long been studied as the basis of anticancer and antiviral therapeutics, but their potential as antiparasitic agents has been neglected until recently.…”
Section: Introductionmentioning
confidence: 99%
“…[11] The T. brucei parasite, responsible for the Human African Trypanosomiasis (HAT) disease, endangers 69 million people across Sub-Saharan Africa, [12,13] and existing therapies suffer from severe limitations including drastic side effects [14] and emerging drug resistance [15] in the parasitic strains.G 4l igands have long been studied as the basis of anticancer and antiviral therapeutics, but their potential as antiparasitic agents has been neglected until recently. [9,16] The handfulo fc ompounds explored to date are primarilyn aphthalene diimide derivatives, already widely studied as the basis of potentialanticancer drugs. Though the activities are promising, the identification of further DNA-binding chemotypes capable of exerting selectivea ntiparasitic activity is of criticalr elevance to exploring this therapeutic hypothesis.…”
Section: Introductionmentioning
confidence: 99%